EFFECTIVENESS OF WARM COMPRESS IN REDUCING LOW BACK PAIN DURING THE THIRD TRIMESTER - Melsa Sagita Imaniar; Sri Wahyuni Sundari (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Pregnant women, 90% experienced low back pain during their pregnancy. When the pain is not treated, it triggers mothers' stress, which affects their sleep, which could worsen the pain. Low-back pain during pregnancy caused by changes in anatomical, hormonal, and stressful structures. There were variations in treating low-back pain during pregnancy, and one of them was using a warm compress. It helped bring out a sense of comfort, reducing pain, reducing and preventing muscle spasms, and giving a warm feel. This study aims to analyze the effect of warm compress against low-back pain during the third trimester. This study conducted in Bungursari Community Health Center from May 2018 to February 2019. This study used a quasi-experiment with pre and post-test control group design. Sample taken used consecutive sampling and obtained 21 respondents of pregnant women in their third trimester. Collected data analyzed using paired t-test. The study results showed an influence on warm compressing in reducing low-back pain during pregnancy (p-value= 0.001). It can be concluded that pregnant women could be applied to warm compression when they had low-back pain.Keyword : low-back pain, pregnancy, warm compress